Chemical composition and anti-inflammatory activity of essential oil and ethanolic extract of Campomanesia phaea (O. Berg.) Landrum leaves. (24th April 2020) - Lorençoni, Mariane Fioroti; Figueira, Mariana Moreira; Toledo e Silva, Marcos Vinicius; Pimentel Schmitt, Elisângela Flávia; Endringer, Denise Coutinho; Scherer, Rodrigo; Barth, Thiago; Vilela Bertolucci, Suzan Kelly; Fronza, Marcio
Abstract: Ethnopharmacological relevance: Campomanesia species are used in folk medicine for anti-inflammatory, -ulcerogenic, -diabetic, -obesity, and many other purposes. Aim of the study: This study aimed to investigate the phytochemical profile and pharmacotherapeutic potential of the essential oil (EO) and ethanolic extract (EXT) of the leaves of Campomanesia phaea in relation to antioxidant and anti-inflammatory effects using chemical methods and in vitro bioassays in cell culture. Materials and methods: Gas and liquid chromatography techniques coupled to mass spectrometry were used to identify the main secondary metabolites. The antioxidant activity was determined by the chemical methods of radical sequestration of 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2, 2′-Azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and by ferric reducing antioxidant power (FRAP); in addition to the protective effect against cellular oxidative damage caused by hydrogen peroxide (H2 O2 ) in macrophage culture. The anti-inflammatory and immunomodulatory activity was evaluated for the influence on the production of nitric oxide and superoxide anion (O2 - ), and by the quantification of proinflammatory cytokines tumor necrosis factor (TNF alpha) and interleukin 6 (IL- 6) through Enzyme Linked Immuno Sorbent Assay (ELISA) technique and inhibition of nuclear factor kappa B (NF-κB) through chemiluminescence. Results: A total of 41 compounds were identified in the essential oil (EO), being ( E )-caryophyllene (14%) and caryophyllene oxide (6.9%) the major compounds. In the ethanolic extract (EXT), three flavonoids from the flavanones group were identified: alpinetin O -dideoxy-hexoside, 5, 7-dimethoxyflavanone and alpinetin. The EO and EXT inhibited the production of O2 - (99.0% and 52.9%) at a concentration of 100 μg/mL, intracellular NO - (50.0% and 51.9%) and proinflammatory cytokines IL-6 (41.0% and 82.9%) and TNF-α (74.7% and 87.9%) at a concentration of 50 μg/mL, respectively. In addition, inhibition of nuclear factor kappa B (EO 36.2% and EXT 40.9%) was observed at 20 μg/mL. Conclusions: Taken together, the results indicated that EO and EXT possess potent anti-inflammatory activities and it may hold therapeutic promise in the management of acute and chronic inflammatory conditions. Graphical abstract: Image 1